(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. - La fisionomia del diritto di libertà religiosa nello spazio europeo: due sistemi a confronto - 2. La giurisprudenza della Corte europea dei diritti dell’uomo in materia di libertà religiosa individuale: le nuove prospettive sul divieto di porto di simboli religiosi - 3. La Corte di giustizia e la libertà religiosa: l’(apparente) risvegliato interesse - 4. Brevi considerazioni conclusive. Freedom of religion before European Courts ABSTRACT: This essay aims to investigate the content of the right to religious freedom in the European Court of Human Rights’ and the EU Court of Justice’s case law. As a matter of fact, the approach of these courts appears to be very different. While in the Strasbourg Court’s case law this right is gradually recognized more and more clearly and the legitimate restrictions foreseen in the Convention are interpreted with increasing restraint, the Court of Luxembourg rarely applies the right recognized by art. 10 of the EU Charter of Fundamental Rights in a direct way and often decides the cases through the lenses of an extensive interpretation of the EU anti-discrimination law.